Safe design and operation of process vents and emission control systems (CCPS concept book., 2006)
Process vent header collection systems are subject to continually varying compositions and flow rates and thus present significant challenges for safe design. Due to increasingly demanding safety, health, environmental, and property protection requirements, today's industrial designers are faced with the need to create increasingly complex systems for more effective treatment, dispersal, or disposal of process gases. Safe Design and Operation of Process Vents and Emission Control Systems provides cutting-edgeguidance for the design, evaluation, and operation of these systems, with emp.